Walking among Pharaohs George Reisner and the dawn of modern Egyptology - Manuelian, Peter Der 1959- (Oxford University Press, 2023)
In this expansive new biography of George Reisner, Egyptologist Peter Der Manuelian examines the life and work of America's greatest archaeologist. Manuelian presents Reisner's undeniable impact and considers his life within the context of Western colonialism, racism, and nationalism.
Keywords: Reisner, George Andrew -- 1867-1942; Ägyptologie; Biografie